Engaging stakeholders, shaping AI ethics: Targeted engagement in corporate AI ethics statements - Meng Ye; Eric Friginal (PLoS ONE, 2026)
Corporate AI ethics statements are being increasingly integrated into sustainability communication to showcase responsible AI performance as part of broader sustainable efforts. This study examines how leading AI companies (developers and adopters) engage with diverse stakeholders through their AI ethics statements. Integrating stakeholder theory with the engagement system, it analyses how Strategic, Responsive, and Operational engagement strategies address the needs of primary and secondary stakeholders. The analysis included 122 English-language statements (265,952 words) from those firms, covering their AI ethics guidelines and policies, press releases, and corporate AI ethics reports. The findings show statistically significant differences in usage frequencies in how primary and secondary stakeholders communicated with targeted engagement strategies. For primary stakeholders, particularly customers and third-party developers, companies frequently used three Operation-targeted strategies to detail data protection measures and AI ethics-related product updates. When addressing corporate management and local regulators, Responsive Acknowledge and Strategic Endorse were more prevalent. In contrast, communication with secondary stakeholders, particularly society, interest groups, and academia, frequently used Strategy-targeted engagement to outline broader ethical AI development plans. These findings inform the development of a stakeholder-oriented engagement model for corporate disclosures on their own trustworthy AI practices.